Incidence, characterization, and impact of newly detected donor‐specific anti‐HLA antibody in the first year after pediatric heart transplantation: A report from the CTOTC‐04 study. Issue 9 (24th March 2018) - Dipchand, A. I.; Webber, S.; Mason, K.; Feingold, B.; Bentlejewski, C.; Mahle, W. T.; Shaddy, R.; Canter, C.; Blume, E. D.; Lamour, J.; Zuckerman, W.; Diop, H.; et al.
Abstract : Data on the clinical importance of newly detected donor‐specific anti‐HLA antibodies (ndDSAs) after pediatric heart transplantation are lacking despite mounting evidence of the detrimental effect of de novo DSAs in solid organ transplantation. We prospectively tested 237 pediatric heart transplant recipients for ndDSAs in the first year posttransplantation to determine their incidence, pattern, and clinical impact. One‐third of patients developed ndDSAs; when present, these were mostly detected within the first 6 weeks after transplantation, suggesting that memory responses may predominate over true de novo DSA production in this population. In the absence of preexisting DSAs, patients with ndDSAs had significantly more acute cellular rejection but not antibody‐mediated rejection, and there was no impact on graft and patient survival in the first year posttransplantation. Risk factors for ndDSAs included common sensitizing events. Given the early detection of the antibody response, memory responses may be more important in the first year after pediatric heart transplantation and patients with a history of a sensitizing event may be at risk even with a negative pretransplantation antibody screen. The impact on late graft and patient outcomes of first‐year ndDSAs is being assessed in an extended cohort of patients. Abstract : The authors use a large multi‐institutional cohort to establish the incidence, pattern, and early clinical impact of newly detected donor‐specific antibodies after pediatric heart transplantation. Also see an editorial from Pajaro et al onpage 2107, and related CTOTC articles onpages 2135 and2148 .